2019
DOI: 10.3892/ol.2019.10603
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on superb microvascular imaging and conventional ultrasonography in differentiating BI‑RADS 4 breast lesions

Abstract: This prospective study aimed to explore the diagnostic value of superb microvascular imaging (SMI) in differentiating Breast Imaging Reporting and Data System (BI-RADS) 4 breast lesions compared with conventional ultrasonography (US). A total of 111 patients with 116 breast lesions underwent grayscale ultrasound (US), colour Doppler flow imaging (CDFI) and SMI breast imaging between February 2016 and May 2018. CDFI and SMI were performed to evaluate vascular quantity, morphology, and distribution characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 25 publications
0
32
0
2
Order By: Relevance
“…We reviewed the titles and abstracts of all articles and excluded 21 articles; full texts and data integrity were also reviewed and 11 were further excluded. Finally, 15 studies that met all inclusion criteria were included in this meta-analysis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Figure 1 showed the selection process of eligible articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…We reviewed the titles and abstracts of all articles and excluded 21 articles; full texts and data integrity were also reviewed and 11 were further excluded. Finally, 15 studies that met all inclusion criteria were included in this meta-analysis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Figure 1 showed the selection process of eligible articles.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Only 1 prior study has reported a case of calcifications in lung cancer metastatic to the breast (13). Color blood flow signal was detected in 2 patients, which is different from the abundant vascularity of primary breast carcinoma (21). Sippo et al (20) and Moreno-Astudillo et al (22) reported that the US manifestation of other cancer metastases to the breast were round or oval hypoechoic lesions, which could be diagnosed as benign nodules.…”
Section: Discussionmentioning
confidence: 98%
“…Here, recently published articles can provide this information and be used for reference. A published article reported that the AUC of malignancy detection by B-mode US was only 0.698 in differentiating BI‑RADS 4 breast lesions 35 . For the human readout performance of malignant lesions classification in US image, the AUC from several previous studies and using similar estimated methods was between 0.6 and 0.91, and PPV (from 0.46 to 0.81) and sensitivity (47–85%) varied widely.…”
Section: Discussionmentioning
confidence: 99%